2002
DOI: 10.1309/2y7x-ydxk-006b-xlt2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Changes in Anorexia Nervosa Are Correlated With the Amount of Weight Loss and Not With Other Clinical Findings

Abstract: We describe a retrospective study of 4 cases of sporadic fatal infectious mononucleosis (IM), 1 case of fatal IM, and 1 case of sporadic severe IM. Patients were 26 months to 17 years old; 3 were male. Five died of complications of IM. All 5 of these patients had the Epstein-Barr virus (EBV) present in examined tissue specimens; EBV was monoclonal in 3 patients and biclonal in 1. EBV clonality studies were not performed in the remaining patient. All 5 patients also had monoclonal gene rearrangements. The sixth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
116
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 14 publications
9
116
2
1
Order By: Relevance
“…In contrast to IMAT and pancreatic adipocytes, the amount of BMAT does not correlate with total body fat (Di Iorgi et al, 2008;Hardouin et al, 2016;Justesen et al, 2001;Shen et al, 2007), even though a positive correlation between visceral adiposity and vertebral BMAT has been reported for obese premenopausal women (Bredella et al, 2011). Moreover, BMAT is not catabolized during acute starvation but increases during conditions of prolonged caloric restriction, including anorexia nervosa (Abella et al, 2002;Bredella et al, 2009;Cawthorn et al, 2016;Devlin et al, 2010;Ecklund et al, 2010;Moyer-Mileur et al, 2008). The metabolic role of BMAT is not well understood; however, aging-associated increases in BMAT result in reduced bone mineral density (Griffith et al, 2012;Kugel et al, 2001).…”
Section: Beyond Vat and Sat -Other White Adipose Tissue Depotsmentioning
confidence: 99%
“…In contrast to IMAT and pancreatic adipocytes, the amount of BMAT does not correlate with total body fat (Di Iorgi et al, 2008;Hardouin et al, 2016;Justesen et al, 2001;Shen et al, 2007), even though a positive correlation between visceral adiposity and vertebral BMAT has been reported for obese premenopausal women (Bredella et al, 2011). Moreover, BMAT is not catabolized during acute starvation but increases during conditions of prolonged caloric restriction, including anorexia nervosa (Abella et al, 2002;Bredella et al, 2009;Cawthorn et al, 2016;Devlin et al, 2010;Ecklund et al, 2010;Moyer-Mileur et al, 2008). The metabolic role of BMAT is not well understood; however, aging-associated increases in BMAT result in reduced bone mineral density (Griffith et al, 2012;Kugel et al, 2001).…”
Section: Beyond Vat and Sat -Other White Adipose Tissue Depotsmentioning
confidence: 99%
“…In four large retrospective studies, incidence of leukopenia ranged from 22% to 36%, anemia from 21% to 39%, and thrombocytopenia from 5% to 11.3% [3][4][5][6][7][8] . The cumulative incidence of bipenias or pancytopenia is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al described a 12-year-old female with AN and complete serous atrophy of her bone marrow but interestingly, no significant peripheral cytopenias [15] . Abella et al reported that often the bone marrow changes are not correlated with peripheral counts [6] . Our patient's peripheral cell counts were much higher than would be expected with a 10% hypocellular marrow with significant serous atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Une anémie arégénérative, normochrome et normocytaire doit faire envisager la pratique d'un myélogramme et si celui-ci n'est pas contributif, la réalisation d'une biopsie ostéomédullaire [7].…”
Section: Discussionunclassified